Exploring age and gender differences of computational thinkers in primary school: A developmental perspective - Jiang, Shan; Wong, Gary K. W. (Journal of computer assisted learning, 2022)
Over the past decade, the call to foster computational thinking (CT) in every child has received considerable attention. However, there is little understanding of whether children are developmentally ready to think computationally and what specific CT concepts and skills can be developed at various ages. This study explored the developmental and gender differences in CT skills of 197 Grade 4–6 students (aged 9–13) before being exposed to instruction and investigated the age–gender interaction effects on their CT acquisition in an intervention combining both programming and non‐programming (unplugged) activities. Results show that students' CT skills followed a developmental progression before instruction. Gender difference across ages was insignificant in conditionals, logical operators, pattern recognition and generalization skills. Additionally, students of different ages developed CT differently during the intervention, and their CT acquisition was unaffected by gender. Implications for practice and research in CT education were discussed. Lay Description What is currently known about the topic Learning progressions for computational thinking have been defined in K‐12 curricula globally. Engaging in programming and non‐programming (unplugged) activities can increase students' CT skills. Controversial results have been reported on the age–gender interaction effects on CT development. Lack of understanding on children's actual progressive development of CT. What this paper adds A developmental progression was found in CT skills of students aged 9–13. Students aged 12 and above had some a priori understanding of CT. No gender difference across ages existed in conditionals, logical operators, pattern recognition and generalization skills before instruction. Students aged 9–11 benefitted the most from an intervention combining both programming and unplugged activities compared to older students. Students' CT acquisition in the intervention was unaffected by gender. Given the intervention, students aged 9 and above developed conditionals, logical operators and pattern recognition skills. However, generalization skill was developed only for students aged 12 and above. Implications for practice and policy The findings lay the foundation for designing evidence‐based age‐appropriate CT learning progression and pedagogies. Age‐appropriate learning content: Given appropriate learning experiences, students aged 9 and above may be ready to learn certain CT concepts and skills, including conditionals, logical operators and pattern recognition. CT pedagogies: Using programming and unplugged activities to develop CT requires careful consideration of students' cognitive development and gender needs.